Self-assembly of P22 protein cages with polyamidoamine dendrimer and inorganic nanoparticles. Issue 2 (5th December 2016) - Palchoudhury, Soubantika; Zhou, Ziyou; Ramasamy, Karthik; Okirie, Franklin; Prevelige, Peter E.; Gupta, Arunava
Abstract: Abstract : Protein cage based nanoarchitectures hold great potential in the fields of energy, catalysis, and bio-applications owing to their ability to tune material's properties in a benign biomimetic approach. We demonstrate the self-assembly of bacteriophage P22 using inorganic nanoparticles and dendrimers for the first time. Inorganic nanoparticles (iron oxide, CoFe2 O4, and Au) and polyamidoamine serve as model systems for rigid and soft linker materials, respectively, to induce P22 assembly via electrostatic interaction. We observed distinctly different packing of P22 using nanoparticles as compared to the polyamidoamine polymer. Notably, the ratio of nanoparticle: P22 and ligand packing on the nanoparticle surface are dominant controls for this assembly. The best results are obtained at 6.5:1 nanoparticle:P22 number ratio in the presence of 50 mM NaCl, pH = 6. In contrast, dense area assembly of P22 is observed at 8:1 polyamidoamine:P22 number ratio with 1 M NaCl (pH ∼ 7.5) for the dendrimer.